Learning with simulations: Influence of a computer simulation with hand- on activities on students' learning of the physics capacitors' concepts - Fouad Mounier Yehya; Aziz M. Barbar; Suzanne Abou-Rjelil (Research in Social Sciences and Technology- OpenED Network, 2019)
The persistence of this study was to investigate the contribution of a computer simulation to students' learning of physics concepts (charging and discharging of capacitors). Interactive computer simulation (Crocodile simulation) was used to spread over the aim of this study. This attempt assesses the progress in understanding the concepts by grade 11 Scientific section after four complete periods (200 minutes) in two different situations: 1- using only a computer simulation; 2-using computer simulation with hands-on activities. The progress was measured through post-test. The results of both descriptive and inferential statistics show that the learners' understanding of capacitors' concepts that can be enhanced and were highly achieved when learners used the computer simulation combined with hands- on activities. The use of Hands-on activities was identified as the cause of this differentiation.